Analisis Yuridis Hak Ahli Waris atas Harta Peninggalan dalam Sengketa Waris di Pengadilan Negeri Jakarta Pusat: Studi Putusan Nomor 174/Pdt.G/2023/PN Jkt.Pst. - Rayi Kharisma Rajib; Muhammad Sultan Ulil Albab; Na’il Febrian Achmad (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Inheritance disputes are a common type of civil dispute in society because they involve the distribution and use of a decedent’s estate. In the Decision of the Central Jakarta District Court No. 174/Pdt.G/2023/PN Jkt.Pst, the dispute arose after two biological children sued their own siblings regarding the administration of their parents’ estate, namely the late Iksan Utojo and the late Livia Utojo. The main issue in this case lies in the obstruction of the process of managing and utilizing the estate because one of the heirs was unwilling to sign the inheritance declaration. As a result, the plaintiffs faced difficulties in handling the administrative matters and utilizing the estate for the family’s livelihood and future. Therefore, Judgment No. 174/Pdt.G/2023/PN Jkt.Pst serves as an important subject of study for understanding the application of civil inheritance law in Indonesia. This study employs a normative legal method using both a statutory approach and a case-based approach. The statutory approach was conducted by examining the inheritance law provisions in the Civil Code (KUHPerdata), while the case-based approach was conducted through an analysis of Judgment No. 174/Pdt.G/2023/PN Jkt.Pst along with the panel of judges’ legal considerations. The primary legal sources used in this study consist of the Civil Code and the court decision that is the subject of the study. In addition, this study also utilizes secondary legal sources, including books, journals, and expert opinions related to inheritance law and the resolution of civil disputes. The research findings indicate that the parties in the case were proven to be the lawful heirs of the same decedents, namely the late Iksan Utojo and the late Livia Utojo. The subject of the dispute in this case was also proven to be the estate or inheritance assets that must be distributed among all heirs. Based on the legal considerations made, the court ruled that each heir has an equal right to the estate, so that each heir receives a share of 1/3 of the total estate. This ruling demonstrates the importance of the court’s role in providing legal certainty and protecting the rights of heirs in accordance with the provisions of the Civil Code.